#TITLE_ALTERNATIVE# - AZIS FADILAH (nim : 15114025), WIDIATMOKO
The 3D model of the city/landscape, must consist of man-made objects (buildings), natural objects (vegetation), and terrain. However, currently 3D modelling cities such as CityGML, still focus on the representation of building geometry. In fact, vegetation is important to model in the city (landscape) because it can be used as a visualization and analysis tool for forestry and landscape planning. 3D models can be built using field data acquired using terrestrial laser scanner (TLS) technology and close-range photogrammetry (CRP) techniques. The technology is able to produce data in the form of cloud point from tree to tree parts such as stems and leaves. However, TLS technology is still quite expensive, so testing is done using CRP techniques that may replace the use of TLS. In this final project, research is done to obtain best field data acquisition method between CRP technique with TLS technology and combined with photo UAV data to produce tree size parameters such as position, stem and crown diameter, height of crown and tree height, and geometry model 3D tree with the most appropriate level of detail. There is also a conversion of tree cloud point to 3D tree model in CityGML environment. The acquired accuracy of tree diameter size compared with field data of 14.8 cm for CRP data and 1.3 cm for TLS data. While the comparison of tree height between CRP and TLS data is 51.2 cm. The resulting 3D model can be used for planting and tree maintenance planning, and determine the type of tree to be planted. This Final Project study concluded that CRP can replace TLS role to obtain position, height, canopy diameter and tree type parameters, and 3D tree model used for 3D landscape modelling.